(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The dividends is one of difficult and important decisions taken by the administration in the economic units, because this decision has a direct impact on the investor and economic unity, so the main objective of any investor is achieve earnings, as well as information borne by dividends about the level and efficiency of management to achieving earnings. The aim of the research is explain the effect of the relationship between accounting policies and dividend in the companies listed in the iraq stock exchange, In this research the impact of accounting policies on the dividends was measured by organizing a questionnaire distributed to a sample of employees in companies listed in iraq stock exchange, and the effect of the variables was explained by use the T-Test, And after testing the hypothesis of the research was reached a set of conclusions, The most important of which was the existence of significant relationship between accounting policies and dividends policy in the companies listed in iraq stock exchange, And the research presented a number of recommendations, the most important of which is the need for the legislative and regulatory bodies in iraq, represented by the accounting and auditing standards board to confirm the companies listed on the iraq stock exchange to disclose the accounting policies used to measure the income items from which dividends are paid, And the need to urge companies listed on iraq stock exchange to follow a fixed dividends policy, and maintain stable levels of dividends and in regular dates to avoid negative effects on stock prices in the financial market.